(untitled) - RAHMADIYAH S, NUR (Jurnal Ilmu Manajemen (JIM), 2013)
This study aimed to examine the effect of variable locuscareer, career patterns, job satisfaction and career success. The goalis a hotel employee in Surabaya consisting of 7 hotels. Sample was24 respondents. Career locus has ten indicators in this study, careerpattern has three indicators in this study, has five indicators of jobsatisfaction and career success has five indicators in this study. Thisstudy is a census study, the method of analysis using partial leastsquares analysis (PLS). Hypothesis testing using the model of innercausality test weight which suggests that career locus has asignificant influence on career success and the resulting effect isnegative, to not have a career pattern pangaruh significantly to asuccessful career and the resulting effect is negative, while jobsatisfaction has significant influence and the resulting effect ispositive.Keywords: career locus, career pattern, job satisfaction, career success.